Pengaruh Penambahan Beban Bangunan Terhadap Kestabilan Lereng Pada Ruas Jalan Sei-Wain Km.15 Kelurahan Karang Joang, Kecamatan Balikpapan Utara, Kota Balikpapan - Arief Nugraha Pontoh (PT FORMOSA CENDEKIA GLOBAL, 2022)
The development activities carried out by the community are not accompanied by knowledge of geotechnical engineering, especially when building in the Karang Joang area which is generally a hilly area with a high potential for landslides or landslides. One of the ground movements that caused landslides occurred in RT. 33 Sei-Wain Road Km. 15 which resulted in damage to roads and houses of residents. This study aims to determine the effect of increasing building loads on slope stability. The benefit of the research conducted is to provide an understanding to the community regarding the importance of geotechnical planning in development in slope areas. The research was conducted by collecting existing data and soil parameters at the landslide location. The data is then modeled using a geo-slope program so that the safety value is obtained. The results of the analysis show a decrease in the safety value of 13.7% so that a decrease in the safety number is obtained from 1.686 which is more than 1.5 so that the slope is in a stable condition to 1.455, with a safe number value below 1.5 moderate disturbances can cause the slope to become unstable.